PENGARUH KONSENTRASI ROOTONE-F DAN PANJANG SETEK PADA PERTUMBUHAN Rhododendron mucronatum G. Don. var. phoeniceum - M.S. PUTRI, DYAN (Jurnal Biologi Udayana; Vol 21 No 1 (2017): JURNAL BIOLOGI UDAYANA, 2017)
Rhododendron mucronatum G. Don. var. phoeniceum is one of ornamental plants that have high economic value and aesthetics. Problems that often experienced in propagation this plant are difficulties in producing roots on cutting and limited availability of seeds on the market. This study aims to determine the effect of plant growth regulators (Rootone-F) and length of stem cuttings on the growth of R. mucronatum G. Don. var. phoeniceum. This study employed completely randomized block design with two factors and three replications. The first factor is concentration of Rootone-F (0, 150, 300, and 450 mg/L) and the second factor is length of stem cuttings (15; 25; and 35 cm). The results showed that the concentration of Rootone-F and cuttings length has significant effect (? <0.01) to number of leaves, roots and seedling height; and cuttings length was highly significant (? <0.05) to the seedling height. Rootone-F optimum concentration for the cuttings growth of shoot R. mucronatum G. Don. var. phoeniceum is 450 mg/L which is indicated by the average value of the number of leaves as much as 8.8 leaves, the average value of the number of roots as much as 9.6 and a mean value of 0.90 cm tall seedlings when compared with controls. Cuttings with 35 cm long provide seed growth R. mucronatum G. Don. var. phoeniceum. The highest indicated by the mean number of leaves as much as 6.6 leaves, the average value of the number of roots of 8.6 and a mean value of 0.88 cm additional seedlings height compared to cuttings at 15 cm length and 25 cm.